Susret ili sukob tsivilizatsija na balkanu : mejdunarodni nauçni skup 10-12 Detsembar 1997 = Encounter or conflict of civilizations on the Balkans : international scientific conference December 10-12, 1997 (Beograd ; Novisad)
672 s.